Molecular subtype diagnosis of endometrial carcinoma: comparison of the next-generation sequencing panel and Proactive Molecular Risk Classifier for Endometrial Cancer classifier - Huvila Jutta; Orte Katri; Vainio Paula; Mettälä Tuukka; Joutsiniemi Titta; Hietanen Sakari (W B SAUNDERS CO-ELSEVIER INC, 2022)
The Cancer Genome Atlas -based molecular classification of endometrial carcinoma (EC) has the potential to better identify those patients whose disease is likely to behave differently than predicted when using traditional risk stratification; however, the optimal approach to molecular subtype assignment in routine practice remains undetermined. The aim of this study was to compare the results of two different widely available approaches to diagnosis the EC molecular subtype. EC specimens from 60 patients were molecularly subclassified using two different methods, by using the FoundationOne CDx next-generation sequencing (NGS) panel and using the Proactive Molecular Risk Classifier for Endometrial Cancer (ProMisE) classifier and performing immunostaining for mismatch repair proteins and p53. POLE mutation status was derived from FoundationOne results in both settings. Molecular classification based on ProMisE was successful for all 60 tumors. Microsatellite instability status could be determined based on the NGS panel results in 53 of 60 tumors, so ProMisE and NGS molecular subtype assignment could be directly compared for these 53 tumors. Molecular subtype diagnosis based on NGS and ProMisE was in agreement for 52 of 53 tumors. One tumor was microsatellite stable but showed loss of MLH1 and PMS2 expression. Molecular subtype diagnosis of EC based on the NGS panel of formalin-fixed paraffin-embedded ECs and based primarily on immunostaining (ProMisE) yields identical results in 98.1% (52/53, kappa Z 0.97) of cases. Although results obtained using these two approaches are comparable, each has advantages and disadvantages that will influence the choice of the method to be used in clinical practice.